The Formation of Student Self-Regulation Through the Practice of Worship and Islamic Habituation - Amalia Dwi Rahmawati; Nurul Latifatul Inayati (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
This study aims to identify forms of Islamic activities that support the development of student self-regulation at SMP Muhammadiyah 5 Surakarta. Self-regulation is an individual’s ability to manage behavior, emotions, and thoughts to achieve specific goals; in an educational context, it is crucial for fostering discipline, responsibility, and independent learning among students. This study employs a qualitative approach with a phenomenological perspective, in which phenomena related to self-regulation are explored through various Islamic activities carried out by students in their daily lives at SMP Muhammadiyah 5 Surakarta. Data collection techniques include observation, interviews, and documentation. The results indicate that the development of students’ self-regulation is fostered through various religious practices and Islamic habits, such as Dhuha prayer, Quran recitation, morning dhikr, as well as character development through teachers’ exemplary behavior and regular religious programs. Additionally, students’ involvement in Muhammadiyah-specific activities such as Hizbul Wathan (HW), Tapak Suci, and the Muhammadiyah Student Association (IPM) also significantly contributes to fostering values of discipline, responsibility, solidarity, and leadership. These activities foster self-awareness, emotional control, and internal motivation in students.